The productivity and energetic efficiency of cultivation of sainfoin varieties - S. A. Ignatiev; G. V. Metlina; T. V. Gryazeva; N. G. Ignatieva (Зерновое хозяйство России, 2018)
The decision of the problem of the development of the stable forage production without increasing of the areas with legumes is considered impossible. The creation of a stable fodder base for animal husbandry in the most soil-climatic zones of the country significantly depends on field grass growing. Sainfoin is the most essential crop for field grass growing, that is of great importance for fodder production, biologization of agriculture, energy saving and ecology. The article considers the two-cycled study of forage productivity and bioenergetics efficiency of the sainfoin varieties (developed in ARC ‘Donskoy’) cultivated under heavy shortage of moisture and high average summer temperatures in the south of the Rostov region. The objects of the study were the varieties ‘Manycheskaya’, ‘Rostovskaya 60’, ‘Rostovskaya 90’, ‘Lyutsiya’ and ‘Selyanka’ used for hay. The studied cultivars of sainfoin produced the average yields of green mass of 45.2-50.6 t/ah, 12.0-13.3 t/ha of dry matter, 10.17-11.13 t/ha of fodder units and 2.40-2.65 t/ha of raw protein. The variety ‘Selyanka’ produces the largest yields of green mass - 50.6 t/ha, with 11.13 t/ha of fodder units, 2.65 t/ha of raw protein and 179 g of digestible protein per fodder unit. The variety ‘Lyutsiya’ showed the largest yield of dry matter (13.3 t/ha), 11.9 t/ha of fodder units, 2.63 t/ha of raw protein and 183 g of digestible protein per fodder unit. The assessment of bioenergetics efficiency of sainfoin cultivation showed that the variety ‘Lyutsiya’ possessed the largest content of energy in the yield (143.64 GJ/ha), the net energy income was 112.12 GJ/ha, the least energy capacity of the product was 2.36 GJ/ha and the largest coefficient of energetic efficiency was 4.6. Such indexes of productivity, content of exchangeable energy and digestible protein in dry matter, amount of digestible protein per fodder unit show that the cultivation of each sainfoin variety allows obtaining high-qualitative fodder with 3.8-4.6 coefficient of energetic efficiency.